Kajian Reflektif Pembatik 2021 untuk Perbaikan Pembelajaran Berbasis MOOC - Moch. Abduh; Garti Sri Utami; Sumarno Sumarno (Jurnal Didaktika Pendidikan Dasar, 2022)
Educational technology competence is urgently needed for teachers in the 21st century. As stated by UNESCO ICT Competency Framework for Teacher version 3, the use of ICT technology and basic competencies in 21st-century skills greatly assists teachers in the application of educational technology. This article examines the evaluation of PembaTIK 2021. The purpose of this research is to evaluate PembaTIK 2021 on how to determine the impact of MOOC using Kirkpatrick's four-level training evaluation approach, with studies at two evaluation levels, namely Reaction and Learning Level. This study uses a survey method. The survey was conducted to capture responses from participants in the PembaTIK 2021 Program at Pre-Level and Level 1, most of whom are teachers at all levels of education from 34 provinces in Indonesia. The results show that MOOC effectively achieves increased teacher expertise in educational technology. MOOCs have been successful in changing teachers' attitudes toward the use of basic technology and ICT, creating educational resources for their students, and using innovative teaching approaches in their classrooms. The conclusion is that there has been an increase in teacher ICT competence through ICT-based learning and the MOOC platform.